Genome-Wide Methylation Profiling in the Thalamus of Scrapie Sheep - Hernaiz, Adelaida; Sanz, Arianne; Sentre, Sara; Ranera, Beatriz; Lopez-Pérez, Oscar; Zaragoza, Pilar; Badiola, Juan J.; Filali, Hicham; Bolea, Rosa; Toivonen, Janne M.; Martín-Burriel, Inmaculada (Frontiers in Veterinary Science, 2022)
Scrapie is a neurodegenerative disorder, belonging to the group of Transmissible Spongiform Encephalopathies (TSE). Scrapie occurs in sheep and goats that are considered good natural animal models of these TSE. Changes in DNA methylation occur in the central nervous system (CNS) of patients suffering from prion-like neurodegenerative diseases, such as Alzheimer’s disease. Nevertheless, potential DNA methylation alterations have not yet been investigated in the CNS of any prion disease model or naturally infected cases, neither in humans nor in animals. Genome wide DNA methylation patterns were studied in thalamus obtained from naturally scrapie-infected sheep at a clinical stage (n = 4) and controls (n = 4) performing a whole genome bisulfite sequencing analysis (WGBS). Ewes carried the scrapie-susceptible ARQ/ARQ PRNP genotype and were sacrificed at similar age (4 to 6 years old). Although the average genomic methylation levels were similar between the control and the scrapie animals, we identified 8,907 significant differentially methylated regions (DMR) and 39 promoters (DMP). Gene Ontology analysis revealed that hypomethylated DMR were enriched in genes involved in transmembrane transport and cell adhesion, whereas hypermethylated DMR were related with intracellular signal transduction genes. Moreover, genes highly expressed in specific types of CNS cells and those previously described to be differentially expressed in scrapie brains contained DMR. Finally, a quantitative PCR (qPCR) validation indicated differences in the expression of five genes (PCDH19, SNCG, WDR45B, PEX1 and CABIN1) that matched the methylation changes observed in the genomic study. Altogether, these results suggest a potential regulatory role of DNA methylation in prion neuropathology.